CHARACTERIZATION OF A MODIFIED GRAPHITE ELECTRODE OBTAINED BY HEMIN ELECTROPOLYMERISATION - TURDEAN, Graziella Liana (Studia Universitatis Babeș-Bolyai Chemia, 2015)
A new modified electrode (G/polyHm) was obtained by electropolymerisation of iron (III) protoporphyrin (IX) (hemin, Hm) at the surface of a graphite electrode (G), by repetitive scanning the potential between -0.85 and 0 V vs. Ag/AgCl,KClsat. The cathodic peak revealed by linear sweep voltammetry at the electrode in phosphate buffer, pH 8, corresponds to one electron transfer process occurring at the Hemin(Fe3+)/ Hemin(Fe2+) metallic center of the immobilized hemin. All the estimated electrochemical parameters are in accordance with the values reported for immobilized hemin. The electrode exhibits electrocatalytic properties towards the H2O2 and NO2- reduction, respectively, proving an enzyme-like behaviour of the immobilised hemin, characterised by hyperbolic Michaelis Menten behaviour, when increasing concentrations of substrate were added, irrespective of the scan rate used.